A NOTE ON APPLICATION OF HILLS’ PROCEDURE FOR GROWTH CURVE ANALYSIS OF INDIAN MAJOR CARP, LABEO ROHITA (HAM.), DURING THE GONODAL DEVELOPMENT PERIOD AT SHILLONG, MEGHALAYA - Sarma, D.; Day, S.; Dutta, A. (Journal of Indian Fisheries Association, 2015)
The present study deals with the length increment data of 15 adult Labeo rohita (Ham.) over a period of five months by the applicatin of finite difference method at an altitude of 1496 m above mean sea level at Shilllong, Meghalaya. The technique of repeated measurement has been used frequently to analyse biological growth data (Anderson, 1978). Experiments of this type have broad application, especially in life and social sciences. The alternative approach is the time-series anaylsis including auto regression (Rosner and Munoz, 1988). Basu and Bhattacharya (1996) applied Hills’ (1968) procedure for growth-curve analysis of a freshwater major carp ofindia during the early stages of development. This methodology has predictive capabilities on short and long term bases. The procedure may be summarized in the following lines: